Lipidomic profiling reveals phenotypic diversity and nutritional benefits in Ficus carica L. (Fig.) seed cultivars - Irchad, Ahmed; Ouaabou, Rachida; Aboutayeb, Rachid; Razouk, Rachid; Houmanat, Karim; Hssaini, Lahcen (Frontiers in Plant Science, 2023)
Ficus carica L. seeds are an exceptional source of minor oil, characterized by a high degree of unsaturation and potent antioxidant properties. This study aimed to assess the mineral composition, oil content, and vibrational fingerprints according to the phenotypic diversity in 22 fig genotypes by integrating the FTIR-ATR approach and chemometrics. Results showed the substantial nutritional benefits of fig seeds and their potential utilization in genetic material selection programs, encompassing oil extraction as a minor source of vegetable oil and functional ingredients. By meticulously analyzing the lipochemical profiles, the genotypes were categorized into four distinct clusters. This comprehensive classification not only provides valuable insights into their nutritional composition but also elucidates the inherent similarities and differences among the samples. The findings showed that the studied fig germplasm has high phenotypic diversity, which is probably more genetically related. The studied accessions can be recognized as an important gene pool for future breeding programs and exploring diverse applications for fig seeds. This work will aid in selecting potential genotypes for scientific and industrial purposes. Furthermore, FTIR and chemometrics revealed a notable diversity of patterns, emphasizing the previously overlooked importance of this aspect of the species in evaluating its chemodiversity.